2013 7th International Workshop on Advanced Ground Penetrating Radar 2013
DOI: 10.1109/iwagpr.2013.6601512
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the early-time GPR amplitude technique for electrical conductivity monitoring

Abstract: "In the present paper we use the recently-proposed. early-time GPR (Ground Penetrating Radar) amplitude. technique with the aim of detecting the variations of electric. conductivity in a porous material having a uniform permittivity.. A specific laboratory setup has been realised to evaluate the. sensitivity of the early-time amplitudes to the variations of the. subsurface salt concentration (i.e., conductivity). To assess the. capacity of the early-time amplitude to follow the electrical. conductivity changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…As a test case of loss effects on the ETS behavior, expressed in terms of conductivity σ (or, equivalently, of the imaginary part of permittivity), we have considered a granular medium (glass beads) saturated with solutions having different concentrations of potassium chloride (KCl), to obtain a bulk σ variable between about 0.006 and 0.21 S/m, with ε r = 29 (for further details, see [21]). Examples in Fig.…”
Section: A Laboratory Experimentsmentioning
confidence: 99%
“…As a test case of loss effects on the ETS behavior, expressed in terms of conductivity σ (or, equivalently, of the imaginary part of permittivity), we have considered a granular medium (glass beads) saturated with solutions having different concentrations of potassium chloride (KCl), to obtain a bulk σ variable between about 0.006 and 0.21 S/m, with ε r = 29 (for further details, see [21]). Examples in Fig.…”
Section: A Laboratory Experimentsmentioning
confidence: 99%
“…The waveform amplitude has an inverse linear dependence on the permittivity. In particular, [14] and [15] confirmed that because the first arrival of the GPR signals is strongly dependent on variations in the shallow subsurface permittivity, the signal to noise ratio can be maximized by minimizing the interference from reflections caused by shallow interfaces.…”
Section: Methodsmentioning
confidence: 72%
“…Hence, it is also possible to determine the medium's volumetric water content using an appropriate petrophysical relationship [16,18,23]. configuration, the dielectric permittivity affects both the amplitude and duration of the GPR signal; therefore, higher amplitudes and shorter wavelets are associated with lower permittivity [5,7,8]. The ringing anomalies in the radargrams with very low EM signal amplitudes-due to high attenuation, poor antenna coupling, and temporal stretching-can be analyzed in order to estimate the physical properties of near-surface materials in archaeological as well as cultural heritage sites [4,8,22].…”
Section: Resultsmentioning
confidence: 99%
“…Several controlled experiments, numerical simulations, and "real-life" applications have been conducted to study the effects of EM parameter variations on antenna-material coupling. However, this approach toward evaluating variations in the shallow dielectric permittivity and conductivity (i.e., the presence of moisture) in a soil is more reliable and consistent than other methods [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%